Incidence of the didactic strategy of resolution of problems in the significant learning of Mathematics IV, Civil Engineering at the Private University of Tacna, 2014. - Atencio Vargas, Arcadio (2019)
The objective of this research was to determine the incidence of the application of the problem solving strategy in the levels of achievement of significant learning in the Mathematics IV course, in the Civil Engineering professional career, in the academic semester 2014-I in Private University of Tacna. Of applied type, with a quasi-experimental research design. The study population consisted of 467 students enrolled in the mathematics courses of the career plan of Civil Engineering. The sample consisted of 45 students divided into two groups, one of control and the other experimental. The groups of students were taken in a non-random way, and the sizes were 19 and 26 students respectively. The technique of data collection was the examination and survey, with entrance and exit tests in both groups, questionnaire of perception of the application of the strategy. The results showed that the application of the problem solving strategy, in the Mathematics IV course, allowed to raise the level of achievement of the significant learning, from insufficient (100%) to the level of achievement of very good (69%) and outstanding (15%), making a total of 84% greater than very good, in the students of the fourth cycle of the Civil Engineering career. In conclusion, it was possible to verify that the application of the problem solving strategy has a high incidence on the result of the significant learning, this is evidenced in the results of the exit test, in the students of the experimental group in the course of Mathematics IV, reaching the level of very good.